Pharmacoeconomic analysis of fluid therapy in the treatment of patients with peritonitis - R. I. Yagudina; M. M. Murashko (Фармакоэкономика)
the research work was conducted for the pharmacoeconomic evaluation and optimization of fluid therapy for patients, suffering from peritonitis disease. Reamberin, Ringer's solution, Plasma-Lyte and Sterofundin drugs were compared during the analysis. A cost analysis, cost-effectiveness analysis, budget impact analysis and sensitivity analysis were conducted. The survival rate of patients was used as the effectiveness criterion. The CER amounted to 440,759 roubles for Reamberin, 543,991 roubles for the Ringer's solution, 529,498 roubles for Plasma-Lyte and 502,842 roubles for Sterofundin. The analysis showed that the scheme of peritonitis therapy included Reamberin is the dominant. The « budget impact» analysis was carried out from the perspective of health care facilities. The budget impact analysis shown that the 100% switching patients to Reamberin saves respectively: from the Ringer’s solution 5,654,594 roubles, from Plasma-Lyte 2,215,117 roubles and from Sterofundin 2,218,280 roubles. For the interpretation of the survey data for a particular health facility pharmacoeconomic simulation model was designed.